PENGARUH SERVICE EXCELLENT PETUGAS CHECK IN COUNTER TERHADAP KEPUASAN PENUMPANG PADA BANDAR UDARA INTERNASIONAL HALIM PERDANAKUSUMA - Defi Agustina Indraswari; Arif Fakhrudin (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
In the current era of globalization, airlines are competing to continue to improve the quality of service provided to their passengers with the aim of achieving satisfaction. This research aims to evaluate the effect of excellent service from check-in officers on passenger satisfaction at Halim Perdanakusuma Airport. The research method used is quantitative using a questionnaire as a data collection tool. The number of respondents used was 80 people using Citilink flight services. The sampling technique uses quota sampling. Data were analyzed using the SPSS application using simple linear regression analysis. The research results show that excellent service has a significant influence on passenger satisfaction, with a significance value of less than 0.05. These results show that the level of passenger satisfaction at the airport is positively and significantly influenced by the excellent service quality of the check-in officers. The coefficient of determination (R square) of 0.548 indicates that around 73.8% of the variability in passenger satisfaction can be explained by the variability in excellent service.